Application Of Zeolit And Activated Carbon On Transportation Of Fish Seed (Leptobarbus Hoeveniii Blkr) With Different Densities - Pratama, Wahyu; Harianto, Eko; Arifin, M Yusuf; Pangentasari, Dwinda (Universitas Batangahari Jambi, 2024)
. This study aims to determine the optimum density and to analyze the effectiveness of zeolite and activated carbon additives in the transportation of jelawat fish seed 2-inch for 12 hours. This research was conducted in March-May 2023. Transportation was carried out for 12 hours with the mode of transportation being a 4-wheeled minibus with travel routes starting from Jambi City to West Tanjung Jabung Regency. The experimental design used was a Completely Randomized Design (CRD) with 4 (four) treatments and 3 (three) replications, the treatments given were densities including: treatment A density of 100 individuals/container, treatment B density of 200 individuals/container, treatment C density 300 individuals/container and treatment D at a density of 400 individuals/container. In each container, 20 g and 10 g of zeolite and activated carbon were added. After being transported, the fish were maintained for 14 days. The results showed that during the transportation there were no fish deaths in all treatments so that the survival rate in all treatments was 100%. The average blood glucose level before transportation ranged from 56.3 – 57.3 mg/dL. The survival rate of post-transported barnet fish fry on day 0 to day 7 was 100%, while on day 14 the survival rate ranged from 90.1% -92.3%. Absolute length growth ranged from 1.30 cm/head – 1.38 cm/head. Absolute weight growth ranged from 0.30 gram/head-0.32 gram/head. Blood glucose levels at the start of maintenance ranged from 62.0-87.0 mg/dL. On the 14th day it ranged from 38.3 mg/dL-48.7 mg/dL. The water quality during the transportation and rearing process is still in the optimal range for barley fingerlings